The Management of Food Delivery Systems in the Nutrition Installation at the Hospital - Widiya Nisa (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
One of the important roles of nutrition services is to improve the nutritional status of patients in hospitals so that it is hoped that this can speed up the healing process and shorten the length of stay. The aim of this research is to determine the food management system in order to fulfill patient nutrition at Malahayati Islamic Hospital. This research uses descriptive qualitative research. Data collection techniques by means of observation, interviews using recording and use of documents. Next, the data collected is analyzed. The informants for this research were 4 informants including the head of the Nutrition Installation, staff/nutrition experts and food processing officers and waiters. The sampling technique was carried out using Purposive Sampling. The research results show that the food procurement system starting from ordering and purchasing, receiving, storing and distributing food ingredients is in accordance with PGRS. And food processing starts from menu variations using a 7-day menu cycle, but food presentation and distribution needs to be monitored and evaluated in the use of PPE for waiters. Food procurement system, food processing, food distribution in accordance with PMK No. 78 concerning PGRS and food delivery system management.